Population genetic structure and diversity of the East Balkan Swine (Sus scrofa) in Bulgaria, revealed by mitochondrial DNA and microsatellite analyses. (14th September 2021) - Ishikawa, Keita; Doneva, Radostina; Raichev, Evgeniy G.; Peeva, Stanislava; Doichev, Valentin D.; Amaike, Yosuke; Nishita, Yoshinori; Kaneko, Yayoi; Masuda, Ryuichi
Abstract: The East Balkan Swine (EBS) is the only indigenous pig breed in Bulgaria. We analyzed the mitochondrial DNA (mtDNA) control region and 21 microsatellite loci for 198 individuals from 11 farms in Bulgaria. Obtained 11 mtDNA haplotypes including three novel ones were grouped to two major clades, European clade E1 (146/198 individuals, 73.7%) and Asian clade A (52/198, 26.3%). The mixture of the two clades may have resulted from historical crossbreeding between the European and Asian pig breeds. Clade A was frequent in southeastern Bulgaria (Burgas Province), but less frequent or absent in northeastern Bulgaria (Varna and Shumen Provinces). The distribution of Europe‐ and Asia‐specific haplotypes relative to EBS farm locations could be attributed to regional differences of breeding systems (e.g., crossbreeding with imported commercial pigs). A microsatellite analysis showed high heterozygosities for all the EBS farms, and negative inbreeding coefficients presumably due to crossing with commercial pigs or wild boars and/or efforts to reduce inbreeding by farmers. Bayesian clustering analyses showed that all farm populations are genetically well distinguishable from one another. Although diversity has been maintained by the efforts of farmers and a breeding association, the effective population size remains small, and conservation efforts should be continued.